2018
DOI: 10.1111/imm.12902
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulatory effects of statins

Abstract: SummaryDespite major advances in recent years, immunosuppressive regimens for multiple sclerosis, rheumatoid arthritis, systemic lupus erythematosus and graft-versus-host disease still have major adverse effects and immunomodulation rather than immune paralysis would be desirable. Statins inhibit the rate-limiting enzyme of the L-mevalonate pathway, the 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase. It was shown that blocking the L-mevalonate pathway reduces inflammation through effects on downstream metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(152 citation statements)
references
References 64 publications
(189 reference statements)
1
146
0
5
Order By: Relevance
“…Statins that specifically target the HMG-CoA reductase inhibiting de novo Chol synthesis also display pleiotropic effects (36,37). Statins have been reported to alter mitochondrial function in skeletal muscle (38,39), but the information available regarding the effects on mitochondria in cancer cells is scarce (40).…”
Section: Discussionmentioning
confidence: 99%
“…Statins that specifically target the HMG-CoA reductase inhibiting de novo Chol synthesis also display pleiotropic effects (36,37). Statins have been reported to alter mitochondrial function in skeletal muscle (38,39), but the information available regarding the effects on mitochondria in cancer cells is scarce (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a pleiotropic class of drugs that also exerts several anti-inflammatory effects (43, 544). Despite these anti-inflammatory effects, several studies have now shown statin use to be associated with an increased risk for T2DM (89, 91, 381, 410).…”
Section: Adipose Tissue Inflammation and Insulin Resistancementioning
confidence: 99%
“…Therefore, as well as immunomodulation, COVID-19 treatment should also target reduction of inflammation. In this context, statins have been consistently reported to exert immunomodulatory and anti-inflammatory properties [20][21][22][23][24][25][26][27][28][29][30]. Also, it was previously suggested that statins could enhance host defence and suppress inflammation, thus representing a practical and inexpensive adjunctive or alternative host-directed treatment for infections by viruses, fungi, protozoa, and bacteria [31].…”
mentioning
confidence: 99%